Beyond diagnosis: using PNImodified and composite priority indices to orchestrate meta-skills-driven academic management innovation - Chi Che; Sukanya Chaemchoy; Pruet Siribanpitak (Institute of Advanced Engineering and Science, 2026)
This study translates an academic management–meta-skills integration framework into a data-driven innovation roadmap for private higher education institutions (HEIs) in Sichuan, China. Using an explanatory sequential mixed-methods design, Phase 1 surveyed 400 undergraduates who provided dual ratings of current performance (degree of success, D) and desired priority (importance, I), enabling computation of the modified priority needs index (PNImodified=(I−D)/D) across meta-skills domains and academic management subcomponents. In Phase 2, institutional leaders and senior academics rated the feasibility and impact of aligned innovations; these ratings were integrated with PNImodified to calculate a composite priority index (CPI) and propose phased implementation sequencing. Results indicated the largest perceived meta-skills development needs in adaptive expertise (PNImodified=0.48) and relational dynamics (0.34). At the academic management level, curriculum development (0.56) and evaluation and assessment (0.45) emerged as the most critical domains. Curriculum structuring (0.65), instructional design (0.53), meta-skills evaluation modules (0.59), and learning engagement (0.59) consistently ranked as top subcomponent priorities and were positioned as Phase 1 actions in CPI-based sequencing. Experts rated the overall innovation as highly suitable (M=4.55) and feasible (M=4.53). The combined indices provide a practical decision tool for sequencing meta-skills-oriented academic management innovations in Sichuan private HEIs.